It is time to tackle psychological determinants of obesity and eating disorders - Pietro Crescenzo (Journal of Health and Social Sciences)
At the beginning of 2019, a report by The Lancet placed great emphasis on the need to change diet and food production worldwide, in order to avoid potentially catastrophic damage to the planet [1]. Nutrition is a complex problem, where obesity, undernutrition and climate change interact to challenge the global food system, as about 3 billion people are undernourished or overnourished and food production is exceeding planetary boundaries. As stated by the EAT-Lancet Commission on Healthy Diets for Sustainable Food Systems, nutrition is a global problem that would require a dedicated Sustainable Development Goal (SDG) [2]. Obesity and malnutrition are two sides of the same question and they are probably one of the most evidence of social and economic inequalities in the world today [3]. In developed countries, obesity and overweight are global public health challenges that are devastating health and economy, as they are increasing at an alarming rate, taking into account the fact that childhood obesity affects both developed and developing countries of all socio-economic groups, irrespective of age, sex or ethnicity [4]. Obesity and overweight constitute an important source of morbidity, impaired quality of life and mortality, as they are associated with several cancers, diabetes and cardiovascular diseases [5]. The worldwide prevalence of obesity nearly doubled between 1980 and 2008. In the USA, prevalence of obesity was 39.8% and affected about 93.3 million of adults in 2015~2016 [6]. In Europe, recent data showed overweight affects 30-70% and obesity affects 10-30% of adults [7]. Obesity is a complex condition associated with many medical disorders as well as with psychological and emotional issues, as obese individuals are at high risk of developing psychiatric disorder [8] and given that etiological basis of eating disorders and obesity usually lies in some combination of psychosocial, environmental, and genetic or biological aspects, which often focus on body image problems. Body image perception results from interconnection of psychological, experiential, cultural and social factors. It is well-recognized that individuals who are affected by depression, anxiety or eating disorders have more difficulty controlling their consumption of food, and there are several socio-cultural and economic determinants contributing to how people eat, which may be considered as risk or protective factors to obesity. Moreover, obesity and eating disorders have a certain number of shared risk and protective factors [9]. In this issue of the Journal of Health and Social Sciences, several authors [10-13] showed how psychological determinants need to be considered in the face of eating disorders. According to Pennella and Rubano [10], people who have unhealthy relationships with food are at high risk of developing an eating disorder. Based on the socio-cultural theory, Qutteina et al [11] showed the importance to incorporate media literacy competences for developing more effective public heath interventions. Tatsi et al [12] highlighted the complex relationship with food, which includes cognitive artifacts like emotional regulation and loneliness. From a pedagogical perspective, Lakhan et al showed stimulating small size consumption portion could be useful for improving eating attitudes and behaviour [13]. Obviously, it is urgent to tackle psychological determinants of obesity, activating multidisciplinary interventions.